What a Contemporary Artist Can Bring to an Early Childhood Education Classroom. The Color of Jessica Stockholder (Olhar de Professor, 2025)
This article presents a personal reflection on the potential dialogue between contemporary art proposals and childhood. By way of illustration, it describes an artistic practice carried out with children in early years education, based on the work of the artist Jessica Stockholder. The methodology adopted is qualitative and includes direct observation in the classroom, analysis of the artistic pieces created by the children, and oral records through audio recordings.
Keywords: Early Childhood Education; Contemporary Art; Jessica Stockholder